Data Resource Profile: Public Health Scotland (PHS) Homecare Medicines Dataset: A National Resource for Linked Prescribing Data for Specialist Medicines Prescribed in Hospital Outpatient setting and Supplied Via Homecare Services - Kurdi, Amanj; Stobo, Laura; Millar, Morven; Clayton , Will; Merrick , Andrew; McTaggart, Stuart; Mueller, Tanja; Bennie , Marion (International Journal of Population Data Science, 2026)
Introduction The Homecare Medicines (HCM) dataset is a national, patient-level dataset developed by Public Health Scotland (PHS) to capture the supply of specialist medicines delivered through homecare services in Scotland. These services are a critical component of outpatient treatment pathways, particularly for long-term conditions requiring specialist care, such as inflammatory arthritis, cancer, and immune-mediated diseases. Prior to 2019, data on homecare prescribing were fragmented and locally held, limiting national analyses. Methods The dataset was initially established during the COVID-19 pandemic to identify immunocompromised patients for vaccine prioritisation. Monthly supply-level data are submitted by homecare providers. Each record includes a pseudonymised unique patient identifier, derived through national health person-level data linkage processes and standardised medicine information mapped to the NHS dictionary of medicines and devices (dm+d), including medicine name (brand and/or generic), formulation and supply date, and, where provided, treatment indication. The presence of a unique patient identifier enables deterministic linkage with a range of national datasets, including community and hospital prescribing, hospital admissions, mortality, cancer registry, and demographic indicators. Results The HCM dataset is held securely within the PHS national data infrastructure and accessed via the National Safe Haven. As of April 2025, it includes data from five national providers and covers approximately 98% of the Scottish homecare market. The dataset comprises over 1.3 million supply records for more than 41,000 patients since 2019. Data quality is high for core fields, with missingness levels very low-almost all key variables have <1% missing values-and more than 99.9% of records are successfully indexed with the unique patient identifier. Indication data is partially complete and improving. Medicines are coded using standardised drug dictionaries. Conclusion Access to the HCM dataset is available through eDRIS subject to Public Benefit and Privacy Panel (HSC-PBPP) approval. The dataset is well suited for studies on medicine utilisation, equity in access, treatment outcomes, and service planning. Ongoing improvements include enhanced indication capture and integration with Scotland's wider digital prescribing infrastructure.